The EU referendum, planning and the environment: where now for the UK?. Issue 2 (March 2017) - Cowell, Richard
Abstract : The referendum of 23 June 2016, in which the UK voted to leave the European Union, has potentially far-reaching implications for planning, especially its interface with environmental policy. While the five months since the referendum show stability in the world of planning practice, moves to renegotiate the UK's relationship with Europe raise a number of important questions: will we see an erosion of the firm environmental standards and targets characteristic of EU environmental policy? Will business interests and infrastructure proponents be successful in arguing that Brexit requires yet further growth-supporting measures? How will the evident salience of immigration, sovereignty and identity concerns shape planning and environmental policy? Will the devolved governments thwart or redirect the 'leave' process? Alongside responses to specific institutional changes, planning and environmental bodies will need to respond to a political context in which elites are mistrusted, the benefits of globalisation and supra-national governance are questioned, and 'putting Britain first' is a discourse with increased traction.